2016
DOI: 10.1097/mib.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Self-reported Medication Adherence in Inflammatory Bowel Disease

Abstract: In patients with IBD, a VAS seems the most appropriate tool for quantifying medication adherence in clinical practice. The MMAS-8 may be used additionally to provide insight in specific reasons for non-adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…In our hospital, since 1 September 2019, pharmacists have measured the VAS score of hospitalized patients at admission as routine work and, as a result, have provided better medication counseling to these patients than before. The VAS is used to assess medication adherence and shows high median or mean scores in a variety of populations: patients taking antidiabetes (median, 95.9%) and lipid-modifying (median, 95.2%) drugs [48]; hypertension/type 2 diabetes mellitus/dyslipidemia patients (mean, 91.3%) [51]; patients taking at least one hypertensive medication (median, 100%) [56]; IBD, including ulcerative colitis or Crohn's disease, patients (median, 91-100%) [50,54,57,58]; rheumatoid arthritis patients taking methotrexate (median, 94%) [59]; patients taking warfarin (mean, 92.2-96.6%) [49,60]; patients admitted to the psychiatric ward (mean, 86%) [61]; glaucoma patients (median, 95.0%) [62]; postmenopausal women with hormone receptor-positive breast cancer taking aromatase inhibitors (median, 100%) [63]; human immunodeficiency virus patients undergoing antiretroviral therapy (94-100%) [53,64]. Our median VAS score of 98% was high, similar to previous studies, probably because the study participants were self-administering elderly patients who were highly motivated to take their medications, leading to a high VAS score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our hospital, since 1 September 2019, pharmacists have measured the VAS score of hospitalized patients at admission as routine work and, as a result, have provided better medication counseling to these patients than before. The VAS is used to assess medication adherence and shows high median or mean scores in a variety of populations: patients taking antidiabetes (median, 95.9%) and lipid-modifying (median, 95.2%) drugs [48]; hypertension/type 2 diabetes mellitus/dyslipidemia patients (mean, 91.3%) [51]; patients taking at least one hypertensive medication (median, 100%) [56]; IBD, including ulcerative colitis or Crohn's disease, patients (median, 91-100%) [50,54,57,58]; rheumatoid arthritis patients taking methotrexate (median, 94%) [59]; patients taking warfarin (mean, 92.2-96.6%) [49,60]; patients admitted to the psychiatric ward (mean, 86%) [61]; glaucoma patients (median, 95.0%) [62]; postmenopausal women with hormone receptor-positive breast cancer taking aromatase inhibitors (median, 100%) [63]; human immunodeficiency virus patients undergoing antiretroviral therapy (94-100%) [53,64]. Our median VAS score of 98% was high, similar to previous studies, probably because the study participants were self-administering elderly patients who were highly motivated to take their medications, leading to a high VAS score.…”
Section: Discussionmentioning
confidence: 99%
“…Although medication non-adherence is an important drug-related issue in all populations, it is particularly problematic for elderly patients, who often experience a variety of medical conditions and use more medications compared to other patients [36]. The medication adherence of patients is assessed by evaluating medical/dispensing records and pharmacy claims data, such as the Medication Possession Ratio [37,38] and the Proportion of Days Covered [39][40][41][42]; using electronic monitoring devices [43,44]; using patient self-reports [45], such as the Morisky Medication Adherence Scale [46,47] and the visual analogue scale (VAS) [48][49][50][51][52][53]. The VAS is a tool that helps clinicians or pharmacists assess the medication adherence of patients in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study comparing 3 different tools to measure self-assessed medication adherence of patients with IBD, Severs et al 44 found that the VAS most optimally represented the quantitative variability of adherence, whereas the MMAS-8 and the Forget Medicine Scale might have resulted in overestimation or underestimation of adherence due to unequal differences in outcome possibilities. It was concluded that VAS seems to be the most appropriate tool for quantifying medication adherence in clinical practice and that the MMAS-8 may be used additionally to provide insight into specific reasons for non-adherence.…”
Section: Methods Of Adherence Measurementsmentioning
confidence: 99%